Pemphigoid Gestationis and adverse pregnancy outcomes: A literature review - Tay, Kai Xin; Mohd Firdaus Mohd Hayati; Fairrul Masnah @ Kadir; Win, Win Than; Abdel Mohsen Mohamed Ahmed Abdel Hafez (Elsevier, 2022)
Pemphigoid gestationis (PG), also known as gestational pemphigoid, as it is specifically associated with a pregnancy event, is among the rare pregnancy-related dermatoses, characterised by the formation of autoantibodies against Bullous Pemphigoid antigens 180 and 230 (BP180 and BP230), causing significant damage to the basement membrane of the skin, resulting in marked pruritus and blisters on the abdomen and extremities. Diagnosis of PG is basically made by the characteristic clinical picture and confirmed by immunofluorescence studies and histopathology of a skin biopsy. Treatment, just as for other autoimmune dermatoses, is achieved by corticosteroids with the risk of relapses in subsequent pregnancies. Fetal growth restriction and pre-maturity are potential fetal complications associated with the disease, hence the recommended combined antenatal care by a dermatologist as well as an obstetrician, however, this disease is unlikely to be a source of significant maternal morbidity or mortality.